2017
DOI: 10.1039/c6fo01503d
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of isoliquiritin against corticosterone-induced neurotoxicity in PC12 cells

Abstract: Isoliquiritin, a flavonoid glycoside compound from licorice, possesses a broad spectrum of pharmacological activities including antioxidant, anti-inflammatory and anti-depression activities. However, the neuroprotective mechanisms of antidepressant effects remain unclear. In this study, the aim was to investigate the cytoprotective efficiency and potential mechanisms of isoliquiritin in corticosterone-damaged PC12 cells. The results of this study showed that pretreatment of PC12 cells with isoliquiritin signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 40 publications
5
30
0
Order By: Relevance
“…However, pretreatment with HSR attenuated these changes, indicating that HSR induces mitochondrial protection in vitro. It has been demonstrated that corticosterone induces apoptosis through activation of the caspase-3 apoptosis pathway [40]. Our findings indicate that HSR may exert its therapeutic effects by regulating the mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 55%
“…However, pretreatment with HSR attenuated these changes, indicating that HSR induces mitochondrial protection in vitro. It has been demonstrated that corticosterone induces apoptosis through activation of the caspase-3 apoptosis pathway [40]. Our findings indicate that HSR may exert its therapeutic effects by regulating the mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 55%
“…6,7,12,59 Zhou et al suggested a potential mechanism of toxicity by CORT: CORT causes a large increase in the levels of intracellular ROS, decreases MMP, releases cytochrome C, activates caspase-3, and all of this inducing apoptosis. 53 In our experiment, CORT remarkably increased the number of early and late apoptotic cells, whereas the number of apoptotic cells was considerably reduced aer M 18:3 treatment. Moreover, CORT increased the expression levels of cleaved-caspase-3, Bax, cytochrome C, and cleaved-PARP, and decreased the expression level of Bcl-2.…”
Section: Discussionsupporting
confidence: 49%
“…57,58 Bcl-2 can competitively bind to Bax on the mitochondrial membrane to form a Bcl-2/Bax heterodimer resulting in closing of the MPTPs and preventing the release of proapoptotic factors from mitochondria, thus achieving an antiapoptotic effect. 53 High levels of CORT cause nerve cell apoptosis in vitro and vivo. 6,7,12,59 Zhou et al suggested a potential mechanism of toxicity by CORT: CORT causes a large increase in the levels of intracellular ROS, decreases MMP, releases cytochrome C, activates caspase-3, and all of this inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CORT is the major rodent glucocorticoid, and exposure to continued high CORT concentrations can cause lymphocyte, cortex and hippocampal nerve cell damage (12), which can be reversed by antidepressants. There is also sufficient evidence to suggest that a drug possessing the ability to reverse CORT-induced neurotoxicity may have a possible therapeutic potential in preventing or treating major depression (13).…”
Section: Neuroprotective Effect Of Polysaccharides From Gastrodia Elamentioning
confidence: 99%